Bilateral Simultaneous Avulsion Fractures of the Proximal Tibia in a 14-Year-Old Athlete with Vitamin-D Deficiency - Ziad Harb; Arfan Malhi (Case Reports in Orthopedics)
Fractures involving the proximal tibial epiphysis are rare and form 0.5% of all epiphyseal injuries. The specific anatomical and developmental features of the proximal tibial epiphysis make it vulnerable to unique patterns of fractures. Vitamin-D plays a vital role in bone homeostasis and its deficiency has an impact on fracture risk and healing. We present the first ever reported case of simultaneous bilateral proximal tibial physeal fractures in an athlete with vitamin-D deficiency. Treatment consisted of plaster immobilisation, and the patient made a full recovery and returned to preinjury level of activities. We report this case for its uniqueness and as an educational review of the importance of the developmental anatomy of the proximal tibia. We review the literature and discuss how the stages of the growing physis determine the type of fracture sustained.